2020
DOI: 10.1016/j.catena.2019.104421
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sample size on different machine learning models for groundwater potential mapping in mountain bedrock aquifers

Abstract: Machine learning models have attracted much research attention for groundwater potential mapping. However, the accuracy of models for groundwater potential mapping is significantly influenced by sample size and this is still a challenge. This study evaluates the influence of sample size on the accuracy of different individual and hybrid models, adaptive neuro-fuzzy inference system (ANFIS), ANFISimperial competitive algorithm (ANFIS-ICA), alternating decision tree (ADT), and random forest (RF) to model groundw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(44 citation statements)
references
References 92 publications
4
40
0
Order By: Relevance
“…This is partly consistent with findings by Rahmati et al [20] and Naghibi et al [75], who concluded that RF is a powerful predictive model that can run accurately with large databases and can process thousands of input variables without variable deletion. Similarly, Davoudi Moghaddam et al [29] found that RF prepares estimates of the variables that are vital for classification, is robust with unbalanced datasets and missing data, and offers an experimental technique for detecting variable interactions [57]. In an earlier study in the Bojnourd Watershed, Iran, RF also demonstrated excellent performance in groundwater potential modeling [20] and similar findings have been made in some other areas [75,76].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…This is partly consistent with findings by Rahmati et al [20] and Naghibi et al [75], who concluded that RF is a powerful predictive model that can run accurately with large databases and can process thousands of input variables without variable deletion. Similarly, Davoudi Moghaddam et al [29] found that RF prepares estimates of the variables that are vital for classification, is robust with unbalanced datasets and missing data, and offers an experimental technique for detecting variable interactions [57]. In an earlier study in the Bojnourd Watershed, Iran, RF also demonstrated excellent performance in groundwater potential modeling [20] and similar findings have been made in some other areas [75,76].…”
Section: Discussionmentioning
confidence: 66%
“…In addition, credible knowledge of the relationships between predictor variables (e.g., geo-environmental factors, etc.) and the respective target variable (i.e., groundwater potential) can help decision-makers achieve sustainable groundwater management, but these associations are still somewhat complicated and poorly documented [29]. The results of variable importance analysis using the RF model indicated higher importance of RSP, lithology, TWI, altitude, and drainage density, which shows the significant impact of DEM-derived factors on groundwater potential modeling ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rainfall is one of the most important factors for groundwater potential mapping as it directly affects groundwater recharge [10,12,22]. The yearly average rainfall of this area varies from 4.80 to 7.23 mm (Figure 2j).…”
Section: Groundwater Influencing Factorsmentioning
confidence: 99%
“…Therefore, further research on the exploration and estimation of groundwater potential and resources is necessary for proper water management of an area. Among different management strategies, potential groundwater mapping is an effective approach that can assist managers to adopt more efficient management plans [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%